Employee satisfaction as a support for higher education institutional performance - Dwi Haryanta; Kaswadi; Reza Syehma Bahtiar; Wibowo Amiruddin Hadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Employee satisfaction is a critical factor influencing the performance of higher education institutions. This study aimed to assess employee satisfaction at Universitas Wijaya Kusuma Surabaya, focusing on (a) measuring the level of employee satisfaction, (b) identifying factors hindering employee performance, (c) evaluating the institution’s human resource management practices, and (d) proposing improvement strategies to improve employee performance and support institutional goals. This study used a quantitative research design, with a sample of 72 employees selected through proportional random sampling across various work units. The study assessed six dimensions of employee satisfaction: (1) satisfaction with institutional policies on human resource management, (2) satisfaction with leadership commitment, (3) satisfaction with compensation and welfare, (4) satisfaction with the work environment, (5) satisfaction with career development, and (6) satisfaction with competency development. The findings showed the following results: (a) employees were dissatisfied with institutional policies on human resource management (mean score 2.14), (b) dissatisfied with leadership commitment (mean score 2.28), (c) satisfied with compensation and welfare (mean score 2.54), (d) satisfied with the work environment (mean score 2.54), (e) dissatisfied with career development (mean score 1.82), and (f) dissatisfied with competency development (mean score 1.82). Despite these challenges, employees showed high integrity toward the institution (mean score 3.53). Therefore, it can be concluded that employee dissatisfaction negatively impacted institutional performance, as reflected in the university’s accreditation ranking of B (very good).